Pseudoperonospora cubensis virulence and pathotype structure in Kazakhstan. (16th July 2018) - Rsaliyev, A. S.; Amirkhanova, N. T.; Rametov, N. M.; Pahratdinova, Z. U.; Ojiambo, P. S.; Lebeda, A.
Abstract : Severe epidemics of cucurbit downy mildew caused by Pseudoperonospora cubensis have been observed in recent years in major cucumber‐producing regions in Kazakhstan. However, information on the pathogenic variability of P. cubensis that could facilitate screening of candidate cucumber varieties and hybrids prior to deployment for commercial production is currently not available. A total of 112 isolates were collected from 2014 to 2016 during surveys in three major cucumber‐producing regions of Kazakhstan. Single lesion isolates were tested for their compatibility with a differential host set composed of 12 genotypes. Most isolates were compatible with Cucumis sativus and C .  melo subsp. melo, while none were compatible with Citrullus lanatus . Isolates differed primarily by their virulence to C. pepo subsp. pepo and Benincasa hispida . Based on the patterns of compatibility with the differential host set, 29 pathotypes were identified. Of these, 18 were associated with a specific production region, six occurred in two regions and five were present in all three regions. The number of virulence factors (VF) ranged from 2 to 10, with 65% of the pathotypes having eight or more VFs. Indices of diversity showed that virulence was very diverse within the pathogen populations. Clustering of pathotypes based on similarity in virulence showed the existence of two main clusters. The high pathogenic variability observed in this study suggests that newly developed cucumber varieties and hybrids with resistance to cucurbit downy mildew need to be evaluated against a wide range of pathotypes prior to their deployment for commercial production in Kazakhstan.